Youth and the Environment: Assessing Awareness, Attitudes, and Action - El Messaoudi, Mohammed; Bouftira, Mohamed; Lamiae, Aboulrhit (Journal of Digital Sociohumanities, 2025)
Environmental degradation necessitates urgent action, yet a gap often exists between awareness and behavior, particularly among youth who are crucial for future sustainability. Higher education institutions potentially play a significant role in shaping student environmentalism. This study addresses the persistent disconnect between environmental awareness and consistent pro-environmental action among university students. It specifically investigates factors influencing this gap, including the perceived environmental responsibility of the students' university. The study aimed to: (1) Assess university students' environmental knowledge (particularly regarding marine litter), attitudes, and awareness; (2) Identify factors influencing engagement in specific pro-environmental behaviors; (3) Evaluate how perceptions of university environmental responsibility affect student attitudes and behaviors; and (4) Explore perceived barriers and facilitators to environmental action. This research employed a mixed-methods approach with 122 university students. Quantitative survey data measured environmental knowledge (true/false, multiple choice), attitudes (Likert scales, e.g., interest, worry), and self-reported behaviors (e.g., household actions, waste separation). Qualitative data from open-ended questions explored perceptions of barriers, facilitators, and the university's role. Statistical analyses included descriptive statistics, correlations, t-tests, ANOVA, and regression; thematic analysis was used for qualitative data. Students demonstrated high environmental interest (Mean=4.01/5) and worry (Mean=3.96/5). However, a significant awareness-action gap was evident; for instance, while 81.1% reported using cloth bags, only 39.3% consistently separated household waste. Knowledge varied, with strong understanding of microplastic impacts (89.3% aware of health effects) but misconceptions about local issues (only 41.8% correctly disagreed the Adriatic Sea is clean). Social media emerged as the dominant information source (41%). Crucially, perceived university environmental responsibility significantly influenced student attitudes and behaviors. Qualitative findings highlighted inadequate university infrastructure (e.g., lack of recycling bins, prevalent single-use plastics) as a key barrier. These results underscore universities' critical role in bridging the awareness-action gap. Institutions must actively cultivate environmental responsibility through visible initiatives, improved infrastructure (like accessible recycling), and curriculum integration. Targeted interventions should leverage peer influence, address specific knowledge gaps (e.g., local pollution realities), and translate student concern into tangible, sustainable actions within the campus and community.